Seed bank and optimization in the recovery of degraded areas of Caatinga - Saraiva, Maria Monique Tavares (2023)
The soil seed bank is used as a tool for recomposition of degraded areas, through the improvement and establishment of species, succession and increased biological diversity. Thus, the work evaluated the seed bank of two areas of the Parque estadual Mata da Pimenteira – PEMP and the effect of environmental conditions on seed germination, and their potential for implantation in degraded areas. Soil and litter were collected in two areas (Serra Branca and Pimenteira), which were homogenized, trays and subjected to 70% shading or sun. Seedlings were accounted for and identified. In addition, it determined the density, porosity and speed of basic infiltration (VIB) in the soil in both areas. The emergency relationship, depending on the seed bank and packaging, was evaluated by descriptive and graphical response surface statistics. The relationship between emergence and soil characteristics was observed through correlation. Pimenteira's seed bank showed the highest rate of emergence and diversity. In addition, shading enhances material regeneration. In this context, the insertion of these nuclei-shaped sections in the restoration sectors of the park itself is a potential strategy.